2023
DOI: 10.3390/foods12132455
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Comparative Analysis of Lactiplantibacillus pentosus Isolates Autochthonous to Cucumber Fermentation Reveals Subclades of Divergent Ancestry

Abstract: Lactiplantibacillus pentosus, commonly isolated from commercial cucumber fermentation, is a promising candidate for starter culture formulation due to its ability to achieve complete sugar utilization to an end pH of 3.3. In this study, we conducted a comparative genomic analysis encompassing 24 L. pentosus and 3 Lactiplantibacillus plantarum isolates autochthonous to commercial cucumber fermentation and 47 lactobacillales reference genomes to determine species specificity and provide insights into niche adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…genetic characteristics to L. pentosus and L. paraplantarum [27]. The ANI a commonly used to determine species membership, confirmed that strain JS21 bel L. plantarum, as the calculated ANI value comparing genomes of L. plantarum, L. p and L. paraplantarum was approximately 88%, significantly lower than the 95% cuto for species membership [51,52]. Collinearity analysis was employed to investigate genome correlation by ide homologous sequences and examining their arrangement consistency among d individuals of the same species [53].…”
Section: Functional Genomic Characterizationmentioning
confidence: 70%
See 1 more Smart Citation
“…genetic characteristics to L. pentosus and L. paraplantarum [27]. The ANI a commonly used to determine species membership, confirmed that strain JS21 bel L. plantarum, as the calculated ANI value comparing genomes of L. plantarum, L. p and L. paraplantarum was approximately 88%, significantly lower than the 95% cuto for species membership [51,52]. Collinearity analysis was employed to investigate genome correlation by ide homologous sequences and examining their arrangement consistency among d individuals of the same species [53].…”
Section: Functional Genomic Characterizationmentioning
confidence: 70%
“…The studies show that L. plantarum inhabits various environments with similar genetic characteristics to L. pentosus and L. paraplantarum [27]. The ANI analysis, commonly used to determine species membership, confirmed that strain JS21 belongs to L. plantarum, as the calculated ANI value comparing genomes of L. plantarum, L. pentosus, and L. paraplantarum was approximately 88%, significantly lower than the 95% cutoff score for species membership [51,52]. genetic characteristics to L. pentosus and L. paraplantarum [27].…”
Section: Functional Genomic Characterizationmentioning
confidence: 78%